Experimental Investigation of Wettability of Rock-CO2-Brine for Improved Reservoir Characterization - Arif, Muhammad (Curtin University, 2017)
This work is a collection of experimental wettability data of various rock/CO2/brine combinations including calcite, mica, coals of various ranks, and shales of various TOC. Certain microscopic mechanisms responsible for wettability alteration are also addressed. The system investigated turned less water-wet with the increase in pressure and salinity, and more water-wet with temperature increase. The measured data has direct implications for the structural and residual trapping capacities in the context of geological CO2 storage.